Die nivale Höhenstufe und ein Versuch ihrer klimatischen Abgrenzung anhand ausgewählter Gebiete der Alpen und Skandinaviens - Lehmkuhl, Frank; Böhner, Jürgen; Rost, Karl Tilmann (ERDKUNDE, 1992)
For eight areas in the Alps and three areas in Scandinavia a nivation zone was identified by means of field investigations and the nivation forms were separated from those of the periglacial. Based on the different landscape character, the tendency to the formation or deepening of (nivation) hollows is dominating by different processes and process combinations. On the contrary, there is a lower periglacial zone with more smooth forms and a superficial erosion of slopes caused mainly by solifluction processes. The nivation zone is followed upwards by the glacial one, characterised by bigger forms (cirques) and/or complete covering of the relief by glaciers. The existence of a nivation zone in the Alps and Scandinavia corresponds to mean annual temperatures below -1°C and a seasonal mean temperature of 4°C during May-October. Contrary to the glacial zone, perennial snow patches are mainly linked to hygric conditions. During the ablation period (May-October) the mean precipitation per month is more than 80 mm, and per year 1000 mm, whereby higher temperatures can be compensated by a larger amount of snow. The summer conditions are of special importance as during this period a convergence of maximum weathering and perennial snow patches accentuates the relief forms.